1999
DOI: 10.1021/ma990741o
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Physical Structure and Photophysics for a Liquid Crystalline Polyfluorene

Abstract: From photophysical evidence, we suggest a structural model based on intrachain ordering that can account for the changes of the absorption spectrum of poly(9,9-dioctylfluorene) (PFO) films under certain physicochemical treatment protocols. We correlate this model to the results of X-ray fiber diffraction experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
758
3
20

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 650 publications
(842 citation statements)
references
References 37 publications
(94 reference statements)
61
758
3
20
Order By: Relevance
“…Fig. 3 depicts the fluorescence spectra of BE329 and GE108 at −250, −100, 0, and 100 • C. The spectra are blue-shifted under the sample heating and the vibronic structure is lost as reported for other polyfluorenes [2][3][4]. For GE108 the temperature dependence of the integrated spectra over the entire wavelength range (from 500 to 620 nm), reveals a monotonically decrease of the fluorescence intensity for increasing temperatures, consistent with the Fig.…”
Section: Mechanics Of Relaxation Processes (Solid-state Nmr)supporting
confidence: 83%
See 2 more Smart Citations
“…Fig. 3 depicts the fluorescence spectra of BE329 and GE108 at −250, −100, 0, and 100 • C. The spectra are blue-shifted under the sample heating and the vibronic structure is lost as reported for other polyfluorenes [2][3][4]. For GE108 the temperature dependence of the integrated spectra over the entire wavelength range (from 500 to 620 nm), reveals a monotonically decrease of the fluorescence intensity for increasing temperatures, consistent with the Fig.…”
Section: Mechanics Of Relaxation Processes (Solid-state Nmr)supporting
confidence: 83%
“…It has been observed that the optical and electrical properties of the electroluminescent materials are temperature dependent [1][2][3]. For polyfluorenes these properties were influenced by both the polymer relaxation involving chain segments as well as solid phase transitions when they crystallize or form liquid crystalline phases [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, the fairly rigid fluorene-based π-conjugated polymers and copolymers tend to aggregate, which leads to low solubility, a marked decrease in the photoluminescence quantum yields, and a slight red shift in emission. [10][11][12] Any strategy that breaks up these polymer aggregates and improves their photophysical (particularly the emission quantum yield) properties is of great interest from the point of view of applications of this class of materials. Among the strategies that have been attempted are the incorporation of bulky substituents, 13 introduction of carbazole copolymer units, 14 the interaction with surfactants, [15][16][17] and most recently interaction with nanoparticle assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…[6] However, the blue emission from these materials is often unstable due to the formation of, e.g., ketone defects by oxidation of the methine bridges [7] or aggregate formation. [8,9] Another class of important potential blue emitters for OLEDs are small molecules based on imidazole. [10][11][12] 2,4,5-Triaryl-substituted imidazoles [4 (ref.…”
Section: Full Papermentioning
confidence: 99%